(PVDF)2(PEO)2 miktoarm star copolymers: Synthesis and isothermal crystallization leading to exclusive β-phase formation. (5th October 2022) - María, Nicolás; Patil, Yogesh; Polymeropoulos, George; Peshkov, Anatoly; Rodionov, Valentin; Maiz, Jon; Hadjichristidis, Nikos; Müller, Alejandro J.
Graphical abstract: Abstract: In this work, we study how chain topology can induce different polymorphic behaviors in poly(vinylidene fluoride) (PVDF)-based materials. A linear PVDF precursor with two azido groups at the junction point, (PVDFx -N3 )2 and three 4-miktoarm star copolymers (PVDFx )2 - b -(PEOy )2 with two poly(ethylene oxide) (PEO) and two PVDF arms were synthesized and employed in this study. The amphiphilic miktoarm copolymers were prepared by a combination of anionic ring-opening polymerization, iodine transfer radical polymerization (ITP), and copper-catalyzed azide-alkyne cycloaddition (CuAAC). They have practically similar overall molar mass but different compositions, ideal for performing bulk morphology and crystallization investigations. The isothermal overall crystallization kinetics of the PVDF and PEO arms of the 4-miktoarm star copolymers and representative PEO and PVDF precursors was determined by Differential Scanning Calorimetry (DSC). The results indicate that the star arms crystallized faster than the equivalent precursors as the kinetics are dominated by nucleation effects. The phases formed by the PVDF components in the materials examined were analyzed by studying their melting behavior by DSC, their superstructural morphology by Polarized Light Optical Microscopy (PLOM), and the phase structure by Fourier Transform Infrared Spectroscopy (FTIR). The linear PVDF and (PVDF29 -N3 )2, exhibited α, β and γ-phases (with a majority of β-phase formation) during melting after isothermal crystallization. The ratio of the different phases depends on the crystallization temperature. An analysis of the multiple melting behavior indicated that the sample forms both α and β-phases initially, and the α-phase partially transforms into the γ-phase during isothermal crystallization when the temperature of crystallization increases. We found a remarkable behavior for the 4-miktoarm star copolymers, as the PVDF arms only form the ferroelectric β-phase when all three materials were isothermally crystallized regardless of the crystallization temperature employed. The presence of the polymorphism in the PVDF was detected by DSC, PLOM, and FTIR. Hence, we have shown that tailoring chain topology in PVDF copolymers can lead to exclusive β-phase formation, a path that can be exploited for future piezoelectric applications.